Multiple free radical scavenging reactions of aurones. (October 2021) - Zheng, Yan-Zhen; Deng, Geng; Zhang, Yu-Cang
Abstract: A series of naturally occurring 3′, 4′-dihydroxy aurones have been studied with regard to multiple free radical scavenging reactions in the gas and two liquid phases using density functional theory (DFT). All of the aurones prefer to perform (2 + n)-HAT mechanism to trap 2 + n free radicals, where n is the sum of the numbers of catechol and guaiacyl units in the gas and benzene phases. The second HAT reaction favours occurring in the same catechol moiety of the first HAT mechanism occurring OH group due to the formation of a stable quinone and the highly exothermic step of the final stable product formation. The catechol and guaiacyl moieties show increased potency for the second and fourth H + /e ‒ reactions. In the water phase, aurones can perform multiple H + /e ‒ reactions through n1 PL-ET-n2 HAT-(n+1-n2 )ET mechanism, where n1 is the number of OH groups and n2 is the number of guaiacyl moieties. Graphical abstract: The preferred free radical scavenging mechanism of aurones in different phases. Image 1 Highlights: The antioxidative mechanisms for nine aurones were analysed. Intramolecular hydrogen-bonds can affect the hydrogen atom loss sequence. Aurones can perform multiple H + /e ‒ processes. The preferred mechanisms vary among the different phases.